Biomagnetic Methods: Technologies Applied to Pharmaceutical Research - Cora, Luciana A.; Americo, Madileine F. [UNESP]; Oliveira, Ricardo B. [UNESP]; Serra, Cristina H. R.; Baffa, Oswaldo; Evangelista, Raul Cesar [UNESP]; Oliveira, Giselle F.; Aruda Miranda, Jose Ricardo [UNESP] (Springer/plenum Publishers, 2011)
Biomagnetic methods have been designed for a wide range of applications. Recently, such methods have been proposed as alternatives to scintigraphy for evaluating of a number of pharmaceutical processes in vitro as well as under the influence of gastrointestinal physiological parameters. In this review, physical characterization as well as the most recent applications of Superconducting Quantum Interference Device (SQUID), Anisotropic Magnetoresistive (AMR) and AC Biosusceptometry (ACB) in the pharmaceutical research will be explored. Moreover, their current status and how these technologies can be employed to improve the knowledge about the impact of gastrointestinal physiology on drug delivery in association with pharmacokinetic outcomes, termed pharmacomagnetography, will be presented.
Keywords: drug delivery; gastrointestinal physiology; imaging; pharmacokinetic; solid dosage forms